Correlation between HIV and HCV in Brazilian prisoners: evidence for parenteral transmission inside prison Correlação entre HIV e HCV em prisioneiros brasileiros: evidência de transmissão parenteral no encarceramento - MN Burattini; E Massad; M Rozman; RS Azevedo; HB Carvalho (Universidade de São Paulo, 2000)
OBJECTIVE: It is an accepted fact that confinement conditions increase the risk of some infections related to sexual and/or injecting drugs practices. Mathematical techniques were applied to estimate time-dependent incidence densities of HIV infection among inmates. METHODS: A total of 631 prisoners from a Brazilian prison with 4,900 inmates at that time were interviewed and their blood drawn. Risky behavior for HIV infection was analyzed, and serological tests for HIV, hepatitis C and syphilis were performed, intended as surrogates for parenteral and sexual HIV transmission, respectively. Mathematical techniques were used to estimate the incidence density ratio, as related to the time of imprisonment. RESULTS: Prevalence were: HIV -- 16%; HCV -- 34%; and syphilis -- 18%. The main risk behaviors related to HIV infection were HCV prevalence (OR=10.49) and the acknowledged use of injecting drugs (OR=3.36). Incidence density ratio derivation showed that the risk of acquiring HIV infection increases with the time of imprisonment, peaking around three years after incarceration. CONCLUSIONS: The correlation between HIV and HCV seroprevalence and the results of the mathematical analysis suggest that HIV transmission in this population is predominantly due to parenteral exposure by injecting drug, and that it increases with time of imprisonment. OBJETIVO: É um fato correntemente aceito que as condições de confinamento aumentam o risco de algumas infecções relacionadas às práticas sexuais e/ou ao uso de drogas injetáveis. Realizou-se estudo para estimar a densidade de incidência da infecção pelo HIV na população prisional com aplicação de técnicas matemáticas. MÉTODOS: Foram entrevistados em São Paulo, SP, 631 prisioneiros da maior prisão da América do Sul, que abrigava aproximadamente 4.900 presos na ocasião do estudo. Foi colhido sangue da população entrevistada, analisado o risco para a infecção pelo HIV e realizados testes sorológicos para HIV, HCV e sífilis. Técnicas matemáticas foram usadas para se estimar a densidade de incidência do HIV relacionada ao tempo de encarceramento. RESULTADOS: As prevalências gerais encontradas foram: HIV -- 16%; HCV -- 34%; sífilis -- 18%. Os principais fatores associados à infecção pelo HIV foram a soropositividade ao HCV (OR=10,49) e a confissão do uso de drogas injetáveis (OR=3,36). A análise matemática mostrou que o risco de adquirir a infecção pelo HIV aumenta com o tempo de detenção, atingindo o máximo por volta de 3 anos de aprisionamento. CONCLUSÕES: A correlação entre a soroprevalência do HIV e do HCV e os resultados da análise matemática sugerem que a transmissão do HIV nestsa população se dá preferencialmente pela via parenteral e que seu risco aumenta com o tempo de encarceramento.